Study on Temperature Force Control Mechanism of CRTSⅡ Slab Track: Control Conditions of Temperature Cracking - Long Chen; Jinjie Chen; Jianxi Wang; Jiasheng Cai; Yang Li (Tehnički Vjesnik, 2022)
Diseases such as track slab arching and joint concrete crushing of China Railway Track System (CRTS)II slab track were caused by huge temperature force, which seriously threatens driving safety of trains. In this study, a longitudinal weak connection scheme of CRTSII slab track was proposed to adjust the temperature force in track slab and reduce diseases of longitudinal continuous track slab. This paper focuses on the cracking characteristics of the longitudinal heterogeneous concrete composite structure. The equation which was originally developed to calculate crack width and structure stress under temperature loads, was put forward to consider deformation difference of different elastic modulus. The influence law of various parameters was analyzed. The reinforcement stress and crack width of CRTSII slab track after longitudinal connection weakening were calculated, and the reasonable limit value of tensile force of connection reinforcement and the minimum value of bond resistance of reinforcement in joint position were obtained. The result shows that, in order to reduce the bond resistance between the joint material and the reinforcement, the elastic modulus of the elastic material should be less than 5000 MPa; in order to ensure that the reinforcement does not produce large stress, the elastic modulus of the joint should be greater than 1000 MPa.